Control of Continuous Mixed‐Solution Mixed‐Product Removal Crystallization Processes. Issue 7 (8th June 2017) - Geyyer, Rostyslav; Dürr, Robert; Temmel, Erik; Li, Tao; Lorenz, Heike; Palis, Stefan; Seidel-Morgenstern, Andreas; Kienle, Achim
Abstract: Continuous mixed‐solution mixed‐product removal (MSMPR) crystallization is considered. This process has been studied well, however, different aspects, in particular, process modeling, monitoring, and control remain challenging. An innovative approach for online measurement of the crystal size distribution is presented. Furthermore, unscented Kalman filtering is applied to overcome biased concentration measurement. Finally, a discrepancy‐based control is applied to continuous MSMPR crystallization and its closed‐loop performance is evaluated. Abstract : Some aspects like process modeling, monitoring, and control problems in continuous mixed‐solution mixed‐product removal crystallization are still challenging. An innovative approach for online measurement of the crystal size distribution is proposed. Discrepancy‐based control is designed and applied to a nonlinear model taking system nonlinearities into account.